Supraglottic device for circumventing bag-mask ventilation in giant lip hemangioma - Agrawal, Garima; Singh, Ranju; Nair, Revathy (Indian Journal of Case Reports, 2024)
Congenital hemangiomas are benign tumors of endothelium most often occurring as a solitary lesion with a predilection for the head- and-neck. This report presents a case of a giant friable hemangioma of the lower lip in a 1-month-old male child posted for excision of the lesion. Airway management was challenging as the size, site, and history of repeated local site bleeding made mask ventilation impossible. Bypassing mask ventilation, a supraglottic device (SGD) was directly inserted and adequate lung ventilation was ensured followed by C-MAC® video laryngoscope-guided intubation. Challenging extubation was also overcome by the use of a SGD. This case demonstrates how an airway with impossible bag and mask ventilation can be managed by securing the airway with SGD before intubation.